Costs of and Satisfaction With Child Care Arrangements for Parents of Children With Emotional or Behavioral Disorders. (December 2015) - Barnard-Brak, Lucy; Nuner, Joyce; Sulak, Tracey; Davis, Tonya
Child care arrangements, costs, and satisfaction among parents of children with emotional or behavioral disorders were examined as compared with parents of children with other disabilities. The current study used a large, nationally representative, and community-based sample of approximately 3, 000 parents of children with disabilities aged 3 to 5 years. Results indicate that parents of children with emotional or behavioral disorders did not appear to have significantly different types of child care arrangements or levels of satisfaction with these arrangements as compared with parents of children with other disabilities. Parents of children with emotional or behavioral disorders did appear to spend significantly more on child care as compared with parents of children with other disabilities. Parents of children with emotional and behavioral disorders spent 570 a year as compared with children with other disabilities. The overarching implication for policy would appear to be that special child care subsidies or more publicly fund child care services for parents of children with emotional or behavioral disorders should be provided.